The language of revolution: a study of language change during stasis in Ancient Greek and Roman thought - Sutton, D (2022)
This thesis is an intellectual history of how Ancient Greek and Roman authors understood the relationship between language change and stasis. Focusing on Thucydides, Plato, Sallust, and Tacitus, it chiefly examines the ways they used paradiastole in their accounts of civil conflict. Each author used paradiastole to explore how moral evaluations changed before or during stasis, and how other linguistic changes accompanied it. For each author, paradiastole illuminated the core conflicts of value in stasis, and was therefore central to their analyses. Each author believed they could help understand and rectify these linguistic conflicts, thus preventing stasis or mitigating its effects. Their responses to linguistic conflict reveal a commitment to moral realism, and contrast with Nietzschean accounts of paradiastole.